TONGUE THRUSTING AND OPEN BITE AMONG ORTHODONTIC PATIENTS - A RETROSPECTIVE STUDY - Mathew Thomas Maliael,; M. Naveen Kumar, (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Tongue thrusting in simple terms is the habit of pushing the tongue forward between the upper and lower anterior teeth during deglutition. Tongue thrusting habit has been baffling orthodontists for a long time regarding its role in malocclusion and regarding the approach to intervention in addressing it. This investigation was aimed at identifying the prevalence of tongue thrusting in patients being treated for a malocclusion. A single-center data collection for 490 patients was done. The diagnosis of all cases was reviewed and evaluated by the primary investigator. The cases in which the diagnosis mentioned tongue thrusting was noted. These cases were further reviewed and the diagnosis was evaluated by the second investigator. The attending post-graduate of each case was interviewed and the arch affected and direction of thrust was also noted. The collected data were tabulated into an excel spreadsheet. Pie charts were prepared and the prevalence was calculated. The evaluation and calculation made from the data showed a prevalence of tongue thrusting in orthodontic patients to be 3.87%. Most cases were anterior tongue thrusting and in most cases, the upper arch was affected. The relationship between atypical swallowing and malocclusion demands a multidisciplinary therapeutic approach, orthodontic and myofunctional, to address the condition. Early diagnosis and prompt intervention have a key role in the outcome of therapy and also have a positive influence on the well being of the patient.